How do you measure up? - Pollard, Neil; McDonald, Mary Wilkin, Mike (SRA Santa Rosa, CA, 1994)
Explains patterns in the size of parts of the body and how you can measure your own body to find the patterns. Example: the length of your ring finger equals the length of your ear